Amalgam - Lárus Halldór Grímsson, 1954- (Mnémothèque Internationale des Sciences et Arts en Musique Électroacoustique, 1986)
This composition is music for a ballet, made for the The National Ballet of Iceland and was first performed in November 1986 in Reykjavík. Amalgam is an alloy of mercury. Practically all metals will form alloys of amalgams with mercury, with the notable exception of iron. Amalgams are used as dental materials and as electrodes in various industrial and laboratory electrolytic processes. The ballet was made for six dancers, dressed in gray tight clothes with a golden stripe on the back walking, standing, and dancing on a narrow, strong light beams